Comparison of Finishing Cattle on Self-Feeder or Total-Mixed Ration - J. K. Farney (Kansas Agricultural Experiment Station Research Reports, 2022)
Corn-finished cattle are the backbone of the US beef production system. Traditionally cattle are fed a total-mixed ration (TMR) where all feed ingredients are mixed together, delivered, and fed daily to cattle. Previous research evaluated complete self-fed finishing rations where the diet is placed into a self-feeder. With advancements in technology and varieties of corn, the purpose of this study was to determine the differences in finishing cattle gains, feed efficiency, carcass merit, and cost of production on a TMR ration as compared to a self-fed finishing ration. Thirty-five steers and heifers were sorted into 8 pens and assigned to one of two finishing diet treatments: traditional TMR or self-fed finishing ration. There were 3 pens of heifers and 1 pen of steers per treatment group. There were no differences based on the sex of the cattle. Calves on the self-fed finishing diet had a greater ADG and total gain. Self-fed calves also tended to have a heavier hot carcass weight, greater marbling score, and greater average carcass value than calves on TMR. There was no difference in yield grade. Calves on the self-fed ration had a greater average daily intake and tended to have a higher feed:gain conversion ratio. Cost of gain was 0.58 more for self-fed calves.
Keywords: free-choice finishing; low input finishing